The Languages to Sell in Two Commercial Sites in an Indonesian Small Town - Shierlynda Winnindya Riyandi; Khristianto K (ELLITE, 2021)
The primary goals of this research are to determine the language patterns of the signs, characterize the employment of different languages in these patterns, and explain the language situation reflected by the LL signals in the two locations. It applied a mixed method (Cresswell: 2018). The subject of this research includes shop signs, slogans, and also some of the advertising signs displayed in the sites. The signs were then seen from the number of languages displayed and their source. For the analysis, it adopted the view of Scollon and Scollon and Scollon-Wong (2003). Based on the results of the analysis, the signs can be classified as monolingual, bilingual, or multilingual. The languages displayed there are Indonesian, Javanese, English, Japanese, Arabic. The first three languages are the dominant in any kind of signs collected from these sites. The presence of more than a language in sign has proved that the languages displayed tend to be complement to each other as they bear different information (and sometimes) functions. English is taken for its commerciality and prestige, Indonesian is employed for its communicative role, and Javanese is relied for its shared identity and closeness.